Level of Self-Directed Learning Readiness (SDLR) in Online Learning among Pharmacy Students in Indonesia - Supadmi, Woro; Candradewi, Susan Fitria; Ristiono, Hendy; Utami, Dwi; Mahmudah, Fitri Nur; Perwitasari, Dyah Aryani; Sulisworo, Dwi (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Background: Health science development is currently rapidly changing due to the Covid-19. Changes have taken place not only in terms of scientific development but also in terms of learning methods. Almost all learning methods have shifted into online learning, requiring students to be more active.Objectives: This study aims to determine the level of SDLR among pharmacy students in Indonesia, especially during the pandemic.Methods: The sampling was conducted using an proportional sampling technique based on the distribution of Pharmacy Schools (PTF) in all the provinces in Indonesia. The level of readiness of these pharmacy students was measured using a questionnaire that consisted of four domains. The questions were scored according to the characteristics of the questions (negative or positive).Results: The results of this study showed that 1884 respondents participated in this study. The basic characteristics showed that 89.1% participants were private pharmacy schools and 84.4% of them were female respondents. The mean of each domains of SDLR for self-management, the desire to learn, the emotional competency, and the responsible decision-making was 3.24 ± 2.65, 3.37 ± 2.09, 3.04 ± 1 87, 3.16 ± 2.16, respectively. Based on gender, the difference of mean in sub domain was p=0.000 (need for learning), p=0.002 (hope for outcome), and p=0.000 (identifying problem).Conclusion: In conclusion, the Self-Directed Learning Readiness (SDLR) among pharmacy students in Indonesia is quite high during the pandemic with a score above 3 (scale 1-4).